2002
DOI: 10.1007/s10096-002-0767-4
|View full text |Cite
|
Sign up to set email alerts
|

Wound Infection due to Vibrio vulnificus in Spain

Abstract: Vibrio vulnificus is a gram-negative rod that can cause septicaemia and skin lesions, usually in patients with underlying illnesses such as chronic liver disease or diabetes mellitus. Infections caused by this bacterium are unusual in Spain. A case of skin infection due to Vibrio vulnificus is reported in a patient whose abraded skin on his left leg came into contact with seawater. The patient died suddenly, probably due to septicaemia or bacteraemia caused by this organism. Vibrio vulnificus infection must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…V. vulnificus infections have been reported in diverse climate zones throughout the world (Table 1) including Denmark, Sweden, Germany, Spain, Turkey, Holland, Belgium, Israel, Italy, Korea, Japan, Taiwan, India, Thailand, Australia, and Brazil (Oliver et al, 1983; Dalsgaard et al, 1996; Bisharat et al, 1999; Torres et al, 2002; Oliver, 2006a,b, 2013; Patridge et al, 2009; Huehn et al, 2014; Karunasagar, 2014). This bacterium is commonly found in seafood samples with studies having reported that 3.5–8% of seafood samples in Europe, 2.4% of shrimp from Southeast Asia, 75% of freshly harvested oysters in India and 100% of oysters harvested from the Gulf of Mexico during warm months (May to October) contained V. vulnificus (Jones, 2014).…”
Section: Occurrence Of Vibrio Vulnificusmentioning
confidence: 99%
“…V. vulnificus infections have been reported in diverse climate zones throughout the world (Table 1) including Denmark, Sweden, Germany, Spain, Turkey, Holland, Belgium, Israel, Italy, Korea, Japan, Taiwan, India, Thailand, Australia, and Brazil (Oliver et al, 1983; Dalsgaard et al, 1996; Bisharat et al, 1999; Torres et al, 2002; Oliver, 2006a,b, 2013; Patridge et al, 2009; Huehn et al, 2014; Karunasagar, 2014). This bacterium is commonly found in seafood samples with studies having reported that 3.5–8% of seafood samples in Europe, 2.4% of shrimp from Southeast Asia, 75% of freshly harvested oysters in India and 100% of oysters harvested from the Gulf of Mexico during warm months (May to October) contained V. vulnificus (Jones, 2014).…”
Section: Occurrence Of Vibrio Vulnificusmentioning
confidence: 99%
“…Mortality rates can reach as high as 50%, with extreme morbidity among survivors, including amputations, surgical tissue debridement, and long hospital stays (1)(2)(3). Although the disease remains rare, the incidence of V. vulnificus is rising because of global warming (6,7) and the geographical area impacted by V. vulnificus in the water and food supply is expanding (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…It erupted due to changes in fish marketing policies where tilapia fish were sold live in freshwater instead of dead and packed in ice (Bisharat and Raz, 1996). Had this not occurred, the emergence of biotype 3 may have gone undetected, causing only sporadic cases as occurred in some European countries (Melhus et al, 1995;Dalsgaard et al, 1996;Garcia Cuevas et al, 1998;Horre et al, 1998;Torres et al, 2002;Mitra, 2004;Frank et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the vast majority of human disease has been reported from USA and Southeast Asia due to dietary habits of eating raw or undercooked seafood (Tacket et al, 1984;Klontz et al, 1988;Park et al, 1991;Chuang et al, 1992;Kumamoto and Vukich, 1998;Chiang and Chuang, 2003;Matsumoto et al, 2010). Reports from other parts of the world have been largely sporadic and typically due to wound infection (Bock et al, 1994;Melhus et al, 1995;Dalsgaard et al, 1996;Horre et al, 1998;Torres et al, 2002;Frank et al, 2006).…”
Section: Introductionmentioning
confidence: 99%